1999
DOI: 10.1038/sj.bjc.6690270
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of lipophilic quinazoline-based folic acid analogues: cytotoxic agents with a folate-independent locus

Abstract: Thymidylate synthase (TS; EC 2.1.1.45) is a critical enzyme in the de novo synthesis of thymidylate (dTTP) and has long been recognized as a target for chemotherapeutic intervention. Of interest has been a class of quinazoline-based compounds that fall into three general biochemical sub-type of antifolate TS inhibitor; those which:1. are transported into the cell via the reduced folate carrier (RFC) and are subsequently polyglutamated by folylpolyglutamate synthetase (FPGS; EC 6.3.2.17), e.g. Tomudex TM (ralti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The cell line W1L2:R865 is resistant to a lipophilic quinazoline-based aminomethyl pyridine compound, CB30865, and is associated with amplification at 7q22, as determined by CGH (8). Hybridization of cDNA to chromosomes generally results in signals that are difficult to detect because of the small target footprint of coding sequence in the genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell line W1L2:R865 is resistant to a lipophilic quinazoline-based aminomethyl pyridine compound, CB30865, and is associated with amplification at 7q22, as determined by CGH (8). Hybridization of cDNA to chromosomes generally results in signals that are difficult to detect because of the small target footprint of coding sequence in the genome.…”
Section: Resultsmentioning
confidence: 99%
“…The cell line W1L2:R865 is resistant to the compound CB30865 and derived from the leukemic WIL2 cell line (8). Four rhabdomyosarcoma (RMS) cell lines were used in the study: SCMC-RM2 (9), RH30 (10), RMS (11), and RD (from the American Type Tissue Culture Collection).…”
Section: Methodsmentioning
confidence: 99%
“…Although possessing potent anti-tumorigenic activity, CB-30865 did not act via inhibition of thymidylate synthase or other known folatedependent pathways; suggesting a novel locus of action for this compound [112]. A subsequent study looking at three quinazoline-based analogs confirmed that the 3-pyridine structure of CB30865 conferred more potent inhibitory effects than structurally similar 2-pyridine and 4-pyridine compounds [113].…”
Section: Cb-30865mentioning
confidence: 72%
“…| Review www.future-science.com 7q22 [113], which is the location of the NAMPT gene [18]. However, the link between NAMPT and CB30865 was not determined until 2010; using small-molecule affinity purification, a single prominent protein of about 55 kDa was identified in complex with MPI-0479883, a 3-pyridyl analog of CB30865.…”
Section: Cb-30865mentioning
confidence: 97%
“…NAMPT inhibitors. 1, APO866 (activity see Table1); 2, CHS-828 (activity see Table 1); 3, EB 1627 (pro-drug of CHS828); TRON-8 (IC 50 (SH-SY5Y) 3.8 nM)) 23 ; and CB30865 (IC 50 (W1L2) 2.8 nM) 37 .…”
mentioning
confidence: 99%